Impact of margin width on local recurrence after breast conservative surgery following neoadjuvant chemotherapy (Journal of Pharmaceutical Negative Results, 2022)
Background: The main goal of BCS after NAC is complete excision of the tumor with clear margin, however, no clear definition of what constitutes a clear margin has been proposed. An additional challenge for surgeons is the extent of resection especially in good responders to NAC. The aim of this study was to determine the impact of margin width on local recurrence after breast conservative surgery for patients who responded to neoadjuvant chemotherapy. Patients and Methods: This study is a prospective observational cohort study conducted at the National Cancer Institute, Cairo university, Egypt. The study included 75 Egyptian female breast cancer patients who responded to NAC and then assigned to BCS in the period from October 2019 till October 2020. Patients were assessed with regular appointments at the outpatient clinics up to 2 years follow up after surgery.Results: The mean age was 43.8±9.5 years and 65.3 % of patients were in the premenopausal status. All patients (75 cases) had either cT2 or cT3 disease. Clinical nodal disease (cN1-3) was found in 68 patients (90.7%). Radiologic complete response was seen in 31 patients (41.3%). Most patients (85.3%) had a least circumferential margin of more than 2 mm. Positive nodal involvement was confirmed in 22 patients (29.3%). Over 70% of patients had ypT stage 1c or 2 and over 60 % of patients had ypN stage 0. By the end of follow up, four patients developed local recurrence. The unadjusted local recurrence rate was 5.3% and cumulative local recurrence free survival of the whole studied group at 36 months was 94.6%. The least circumferential resection margin (2mm) had no impact on local recurrence free survival.Conclusion: Margin after NAC and BCS is safe according to ‘‘no ink on tumor’’ guideline and we emphasize the resection of the clipped area in cases of cCR and/or rCR, however, further studies with larger sample size and longer duration of follow up are required to mitigate the local recurrence after BCS following NAC.